Application of the Caffolding Method in Increasing Learning of Praiseworthy Moral Material for Yourself in SA Tanjung Kemuning - Yulistianingsih; Yusniawati; Yunus; Yulianti; Iwarzah, Yupantri (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the application of the scaffolding method in improving the understanding and practice of commendable moral material towards oneself in grade IX students at MTs SA Tanjung Kemuning. The scaffolding method is applied by providing gradual guidance that is adjusted to the needs of students until they are able to understand and apply commendable moral values ​​independently. This research approach uses a qualitative method with observation, interview, and documentation techniques. The subjects of the study were 30 grade IX students of MTs SA Tanjung Kemuning and teachers who teach the subject of aqidah akhlak. The results of the study showed that the scaffolding method was effective in improving students' understanding of the concept of commendable morals towards themselves, as well as encouraging them to apply these values ​​in their daily lives